Topological Conjugacy between Two Kinds of Nonlinear Differential Equations via Generalized Exponential Dichotomy - Xiaodan Chen; Yonghui Xia (International Journal of Differential Equations)
Based on the notion of generalized exponential dichotomy, this paper considers the topological decoupling problem between two kinds of nonlinear differential equations. The topological equivalent function is given.